Training principles for power - Haff, G. G. (Strength and Conditioning Journal, 2012)
The ability to express high power outputs is considered to be one of the foundational characteristics underlying successful performance in a variety of sporting activities, including jumping, throwing, and changing direction. Numerous training interventions have been recommended to enhance the athlete's ability to express high power outputs and improve their overall sports performance capacity. This brief review examines the factors that underlie the expression of power and various methods that can be used to maximize power development.